In memoriam: Carl J. Carrano - Frithjof C. Küpper; Eleanor Carrano; Kenneth N. Raymond; Eric Miller; Ricardo Cruz-López; Ana Mijovilovich; Kyoko Yarimizu; Andrew Cooksy; Wes Harris; Shady A. Amin; Alison Butler; John C. Carrano (BioMetals, 2026)
This article is a celebration of the life and work of Carl J. Carrano who, from a childhood in Long Island, New York, built a career in bioinorganic chemistry, especially in the context of metal uptake and halogen metabolism in microbes and marine organisms.

Controls on timescales of soil organic carbon persistence across sub‐Saharan Africa - Sophie F. von Fromm; Sebastian Doetterl; Benjamin M. Butler; Ermias Aynekulu; Asmeret Asefaw Berhe; Stephan M. Haefele; Steve P. McGrath; Keith D. Shepherd; Johan Six; Lulseged Tamene; Ebagnerin J. Tondoh; Tor‐Gunnar Vågen; et al. (Global Change Biology, 2024)
Given the importance of soil for the global carbon cycle, it is essential to understand not only how much carbon soil stores but also how long this carbon persists. Previous studies have shown that the amount and age of soil carbon are strongly affected by the interaction of climate, vegetation, and mineralogy. However, these findings are primarily based on studies from temperate regions and from fine‐scale studies, leaving large knowledge gaps for soils from understudied regions such as sub‐Saharan Africa. In addition, there is a lack of data to validate modeled soil C dynamics at broad scales. Here, we present insights into organic carbon cycling, based on a new broad‐scale radiocarbon and mineral dataset for sub‐Saharan Africa. We found that in moderately weathered soils in seasonal climate zones with poorly crystalline and reactive clay minerals, organic carbon persists longer on average (topsoil: 201 ± 130 years; subsoil: 645 ± 385 years) than in highly weathered soils in humid regions (topsoil: 140 ± 46 years; subsoil: 454 ± 247 years) with less reactive minerals. Soils in arid climate zones (topsoil: 396 ± 339 years; subsoil: 963 ± 669 years) store organic carbon for periods more similar to those in seasonal climate zones, likely reflecting climatic constraints on weathering, carbon inputs and microbial decomposition. These insights into the timescales of organic carbon persistence in soils of sub‐Saharan Africa suggest that a process‐oriented grouping of soils based on pedo‐climatic conditions may be useful to improve predictions of soil responses to climate change at broader scales.

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Blood chemistry and biliverdin differ according to reproduction and tourism in a free-living lizard - Susannah S. French; Erin L. Lewis; Kwanho C. Ki; Zachary E. Cullen; Alison C. Webb; Charles R. Knapp; John B. Iverson; Michael W. Butler (Journal of Comparative Physiology B, 2023)

Correction to: Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)

Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)
Pumas ( Puma concolor ) were eliminated from most of the eastern USA a century ago. In the past couple of decades, their recovery in the West has increased puma dispersal into the Midwest, with some individuals even traveling to the East Coast. We combined published expert opinion data and a habitat suitability index in an analysis that identified 17 areas in the Upper Midwest, Ozarks, Appalachia, and New England that could potentially host puma populations in the future. Thirteen of these were larger than 10,000 km 2 and so likely to ensure a puma population’s long-term genetic health. Further, we quantified patch size, human density, livestock density, percent public land, and a sociocultural index reflecting wildlife values for comparing patches, as well as present a summary of current legislation relevant to puma management in the East. Our work may be useful in identifying suitable areas to restore pumas based not only on the quality of their biophysical habitat, but also on social values conducive to puma-human coexistence.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

On the origin of amphi-enterobactin fragments produced by Vibrio campbellii species - Aneta M. Jelowicki; Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2022)
Amphi-enterobactin is an amphiphilic siderophore isolated from a variety of microbial Vibrio species. Like enterobactin, amphi-enterobactin is a triscatecholate siderophore; however, it is framed on an expanded tetralactone core comprised of four l -Ser residues, of which one l -Ser is appended by a fatty acid and the remaining l -Ser residues are appended by 2,3-dihydroxybenzoate (DHB). Fragments of amphi-enterobactin composed of 2-Ser-1-DHB-FA and 3-Ser-2-DHB-FA have been identified in the supernatant of Vibrio campbellii species. The origin of these fragments has not been determined, although two distinct isomers could exist for 2-Ser-1-DHB-FA and three distinct isomers could exist for 3-Ser-2-DHB-FA. The fragments of amphi-enterobactin could originate from hydrolysis of the amphi-enterobactin macrolactone, or from premature release due to an inefficient biosynthetic pathway. Unique masses in the tandem MS analysis establish that certain fragments isolated from the culture supernatant must originate from hydrolysis of the amphi-enterobactin macrolactone, while others cannot be distinguished from premature release during biosynthesis or hydrolysis of amphi-enterobactin. Graphical abstract

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Negative Food Effect of Danirixin: Use of PBPK Modelling to Explore the Effect of Formulation and Meal Type on Clinical PK - Richard S. Lloyd; Martin I. Hingle; Jackie C. Bloomer; Stephen J. Charles; James M. Butler; Alan Paul; Xiaofeng Zhu; Bruce Miller; Donald D’Amico; Alison Donald; Ruth Tal-Singer; Claire Ambery (Pharmaceutical Research, 2020)

Combined visual and biochemical analyses confirm depositor and diet for Neolithic coprolites from Skara Brae - Andrzej A. Romaniuk; Elsa Panciroli; Michael Buckley; Manasij Pal Chowdhury; Carla Willars; Jeremy S. Herman; Lore G. Troalen; Alexandra N. Shepherd; David V. Clarke; Alison Sheridan; Bart E. van Dongen; Ian B. Butler; et al. (Archaeological and Anthropological Sciences, 2020)
Coprolites (fossilized faeces) can provide valuable insights into species’ diet and related habits. In archaeozoological contexts, they are a potential source of information on human-animal interactions as well as human and animal subsistence. However, despite a broad discussion on coprolites in archaeology, such finds are rarely subject to detailed examination by researchers, perhaps due to the destructive nature of traditional analytical methods. Here, we have examined coprolitic remains from the Neolithic (third millennium BCE) settlement at Skara Brae, Orkney, using a range of modern methods: X-ray computed tomography, scanning electron microscopy, lipid and protein analysis (shotgun proteomics of the coprolite matrix as well as collagen peptide mass fingerprinting of isolated bone fragments). This combined approach minimised destructiveness of sampling, leaving sufficient material for subsequent study, while providing more information than traditional morphological examination alone. Based on gross visual examination, coprolites were predominantly attributed to domestic dogs ( Canis familiaris ), with morphologically identified bone inclusions derived from domestic sheep ( Ovis aries ) and common voles ( Microtus arvalis ). Partial dissection of a coprolite provided bone samples containing protein markers akin to those of domestic sheep. Considering the predominance of vertebral and distal limb bone fragments, Skara Brae dogs were probably consuming human butchery or meal refuse, either routinely fed to them or scavenged. The presumably opportunistic consumption of rodents may also have played a role in pest control.

Correction to: Amphi‑enterobactin commonly produced among Vibrio campbellii and Vibrio harveyi strains can be taken up by a novel outer membrane protein FapA that also can transport canonical Fe(III)‑enterobactin - Hiroaki Naka; Zachary L. Reitz; Aneta M. Jelowicki; Alison Butler; Margo G. Haygood (JBIC Journal of Biological Inorganic Chemistry, 2018)

Amphi-enterobactin commonly produced among Vibrio campbellii and Vibrio harveyi strains can be taken up by a novel outer membrane protein FapA that also can transport canonical Fe(III)-enterobactin - Hiroaki Naka; Zachary L. Reitz; Aneta L. Jelowicki; Alison Butler; Margo G. Haygood (JBIC Journal of Biological Inorganic Chemistry, 2018)

β-Hydroxyaspartic acid in siderophores: biosynthesis and reactivity - Clifford D. Hardy; Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2018)

Siderophores and mussel foot proteins: the role of catechol, cations, and metal coordination in surface adhesion - Greg P. Maier; Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2017)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Take-all decline in New Zealand wheat soils and the microorganisms associated with the potential mechanisms of disease suppression - Soonie Chng; Matthew G. Cromey; Sarah L. Dodd; Alison Stewart; Ruth C. Butler; Marlene V. Jaspers (Plant and Soil, 2015)

Acyl peptidic siderophores: structures, biosyntheses and post-assembly modifications - Michelle P. Kem; Alison Butler (BioMetals, 2015)

Note from the SBIC President - Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2013)

Note from the SBIC President - Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2013)

Note from the SBIC President - Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2013)

Amino acid variability in the peptide composition of a suite of amphiphilic peptide siderophores from an open ocean Vibrio species - Julia M. Gauglitz; Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2013)

Note from the SBIC President - Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2013)

Identification and structural characterization of serobactins, a suite of lipopeptide siderophores produced by the grass endophyte H erbaspirillum seropedicae - Federico Rosconi; Danilo Davyt; Verónica Martínez; Marcela Martínez; Juan Andrés Abin‐Carriquiry; Hannah Zane; Alison Butler; Emanuel M. de Souza; Elena Fabiano (Environmental Microbiology, 2013)
Summary H erbaspirillum seropedicae Z 67 is a diazotrophic endophyte able to colonize the interior of many economically relevant crops such as rice, wheat, corn and sorghum. Structures of siderophores produced by bacterial endophytes have not yet been elucidated. The aim of this work was to identify and characterize the siderophores produced by this bacterium. In a screening for mutants unable to produce siderophores we found a mutant that had a transposon insertion in a non‐ribosomal peptide synthase ( NRPS ) gene coding for a putative siderophore biosynthetic enzyme. The chemical structure of the siderophore was predicted using computational genomic tools. The predicted structure was confirmed by chemical analysis. We found that siderophores produced by H . seropedicae Z 67 are a suite of amphiphilic lipopeptides, named serobactin A , B and C , which vary by the length of the fatty acid chain. We also demonstrated the biological activity of serobactins as nutritional iron sources for H . seropedicae . These are the first structurally described siderophores produced by endophytic bacteria.

Note from the SBIC President - Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2013)

Note from the SBIC President - Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2013)

Note from the SBIC President - Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2012)

Note from the SBIC President - Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2012)

Identification of new members within suites of amphiphilic marine siderophores - Julia M. Vraspir; Pamela D. Holt; Alison Butler (BioMetals, 2011)

Siderophores of Marinobacter aquaeolei: petrobactin and its sulfonated derivatives - Vanessa V. Homann; Katrina J. Edwards; Eric A. Webb; Alison Butler (BioMetals, 2009)

Imaging Escherichia coli using functionalized core/shell CdSe/CdS quantum dots - Matthew D. Hirschey; Yong-Jin Han; Galen D. Stucky; Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2006)

Structure and membrane affinity of new amphiphilic siderophores produced by Ochrobactrum sp. SP18 - Jessica D. Martin; Yusai Ito; Vanessa V. Homann; Margo G. Haygood; Alison Butler (JBIC Journal of Biological Inorganic Chemistry, 2006)

Marine Siderophores and Microbial Iron Mobilization - Alison Butler (BioMetals, 2005)

Photochemical reactivity of siderophores produced by marine heterotrophic bacteria and cyanobacteria based on characteristic Fe(III) binding groups - Katherine Barbeau; Eden L. Rue; Charles G. Trick; Kenneth W. Bruland; Alison Butler (Limnology and Oceanography, 2003)
Siderophores, high‐affinity Fe(III) ligands produced by microorganisms to facilitate iron acquisition, might contribute significantly to dissolved Fe(III) complexation in ocean surface waters. In previous work, we demonstrated the photoreactivity of the ferric ion complexes of several α‐hydroxy carboxylic acid—containing siderophores produced by heterotrophic marine bacteria. Here, we expand on our earlier studies and detail the photoreactivity of additional siderophores produced by both heterotrophic marine bacteria and marine cyanobacteria, making comparisons to synthetic and terrestrial siderophores that lack the α‐hydroxy carboxylate group. Our results suggest that, in addition to secondary photochemical reaction pathways involving reactive oxygen species, direct photolysis of Fe(III)‐siderophore complexes might be a significant source of Fe(II) and reactive Fe(III) in ocean surface waters. Our findings further indicate that the photoreactivity of siderophores is primarily determined by the chemical structure of the Fe(III) binding groups that they possess—hydroxamate, catecholate, or α‐hydroxy carboxylate moieties. Hydroxamate groups are photochemically resistant regardless of Fe(III) complexation. Catecholates, in contrast, are susceptible to photooxidation in the uncomplexed form but stabilized against photooxidation when ferrated. α‐Hydroxy carboxylate groups are stable as the uncomplexed acid, but when coordinated to Fe(III), these moieties undergo light‐induced ligand oxidation and reduction of Fe(III) to Fe(II). These photochemical properties appear to determine the reactivity and fate of Fe(III)‐binding siderophores in ocean surface waters, which in turn might significantly influence the biogeochemical cycling of iron.

Identification of a natural desferrioxamine siderophore produced by a marine bacterium - J. S. Martinez; M. G. Haygood; Alison Butler (Limnology and Oceanography, 2001)
Desferrioxamine B (DFOB, a terrestrial bacterial siderophore) has been used in experiments on waters from iron‐replete areas of the oceans to manipulate the levels of iron available to the biota. Addition of DFOB complexes the available iron (III) and has been suggested to render this complexed iron unavailable to marine microorganisms. We have identified a marine bacterium belonging to the genus Vibrio that produces the siderophore desferrioxamine G. Desferrioxamine G, another known terrestrial siderophore, is very similar in structure to DFOB, differing only by the substitution of a terminal methyl group by a propionic acid moiety. These results could affect the interpretation of DFOB iron‐removal experiments and further suggest that addition of DFOB might not impose iron stress uniformly across the biological community.